DETERMINATION OF AEROSOL MEAN RESIDENCE TIME USING 210Pb AND 7 Be RADIONUCLIDES IN THE ATMOSPHERE OF ISLAMABAD - Ali, N.; Khan, E. U.; Khan, F.; Akhtar, P.; Waheed, A. (The Nucleus, 2010)
The concentrations of 210Pb, 214Pb and 7 Be radionuclides (having radioactive half lives of 22.3 years, 27 min. and 53.29 days, respectively) in 184 surface level air samples of Islamabad (33.38° N, 73.10° E) were measured using the technique of non-destructive gamma-spectrometry on high purity germanium (HPGe) detector. The mean concentrations of 210Pb, 214Pb and 7 Be in the samples were found to be 0.284 ± 0.012 mBq m-3, 631.06 ± 155.47 mBq m-3 and 3.171 ± 0.084 mBq m-3, respectively. The aerodynamic size distribution of 7 Be in the atmospheric aerosols was also determined, using Anderson 1-ACFM cascade impactors, which resulted in the mean diameter of 7 Be-laden aerosols as 0.79 ± 0.12 µm. The mean residence times (MRT) for 210Pb and 7 Be-laden aerosols, thus obtained, were 5.29 ± 0.91 days and 7.18 ± 0.97 days respectively.